P627 Change in urgency among ulcerative colitis patients: Analyses from the SPARC IBD. (27th May 2021) - Lewis, J; Shan, M; Xhou, X; Naegeli, A; Hunter, T
Abstract: Background: The objective of this study was to assess the changes in prevalence and severity of fecal urgency in Ulcerative Colitis (UC) patients at 6-months from their enrollment visit. Methods: Data from patients in the Study of a Prospective Adult Research Cohort with Inflammatory Bowel Disease (SPARC IBD) were analyzed. UC patients that had an enrollment visit and 6-month visit were included in these analyses. Fecal urgency at each visit was assessed on a scale ranging from 0 (none) to 4 (severe). The change in urgency status from enrollment visit to 6-months is categorized as Improvement (decrease of 1–3 points), No Change, or Worsening (increase of 1–3 points). Descriptive statistics and contingency tables were created to summarize baseline characteristics by fecal urgency group. Chi-square tests, Fisher's exact tests, ANOVA and Wilcoxon rank sum tests were conducted to compare the distribution of baseline characteristics between change in urgency groups, with Bonferroni corrections used for multiple comparisons. Results: Data from 272 UC patients were included in this analysis. 25% of UC patients had an improvement in urgency, 54.4% had no change, 20.6% had a worsening of urgency at 6-months from their enrollment visit. When compared to patients that had no change in urgency at 6-months, UC patients that had improvement in urgency were more likely to have a higher baseline UCDAI (p<0.0001), mean daily bowel movements (p<0.0001), mean daily liquid bowel movements (P<0.0001), elevated stool frequency relative to their normal when well (p<0.0001), liquid stool consistency (p=0.0418), blood in stools (p=0.0001), abdominal pain (p=0.0065), moderate/severe fecal urgency (p<0.0001), worse general well-being (p<0.0001), moderate/severe Physician Global Assessment (PGA) (p=0.0013), and steroid use (p=0.0287) (Table 1). When compared to patients with worsening urgency at 6-months, UC patients that had an improvement in urgency at 6-months were more likely to have a higher baseline UCDAI (p<0.0001), mean daily bowel movements (p<0.0001), mean daily liquid bowel movement (P<0.0001), more stool frequency relative to their normal when well (p<0.0001), moderate/severe fecal urgency (p<0.0001), worse general well-being (p=0.0053), and moderate/severe PGA (p=0.0022). There were no statistically significant differences in baseline characteristics between UC patients that had a worsening or no change in urgency at 6-months. Conclusion: Fecal urgency is a common symptom among UC patients. Urgency is not a stable symptom, with nearly 50% experiencing either worsening or improvement over 6-months. Worse disease activity at enrollment in the cohort was associated with improved fecal urgency symptoms over 6-months.